Challenges and Strategic Solutions for Implementing Accounting Systems among Micro, Small, and Medium Enterprises (MSMEs) in Soppeng Regency - Nur Achriaty; Nurmilasari Nurmilasari (GENTARA: management and accounting research, 2026)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in the regional economy, including in Soppeng Regency. However, the implementation of accounting systems in MSMEs still faces various obstacles that impact the quality of financial management and business decision-making. This study aims to identify the challenges faced by MSMEs in implementing accounting systems and to formulate practical solutions to improve the quality of financial record-keeping. The study employs a qualitative descriptive method, utilising data collection techniques such as interviews, observation, and documentation among MSME operators in Soppeng Regency. The findings indicate that the main challenges include low accounting literacy, limited human resources, insufficient use of digital technology, and a lack of awareness regarding the importance of financial reporting. Practical solutions include enhanced accounting training, ongoing mentoring, the use of simple accounting applications, and strengthening the role of local government and universities in supporting SMEs. It is hoped that this research will serve as a reference for the development of SME empowerment programmes focused on improving financial management